TINJAUAN YURIDIS AKTA NOTARIS SEBAGAI AKTA OTENTIK MEMUAT SUATU KETERANGAN PALSU - Monica Belinda Oksavina (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
A notary is a public official who has the authority to make an authentic deed. A notary deed is an authentic deed and has perfect evidentiary power. An authentic deed contains the legal actions of the parties that have been agreed upon and without coercion from any party. Often an authentic deed contains a false statement from the parties to seek profit from that party. Method The approach used in the preparation of this journal is a Normative Juridical approach. The specification of this research is Analytical Descriptive. From the results of the research, it was found that, First, the notarial deed has been drawn up by the outward, formal, and material aspects, the deed must be considered valid and binding on the parties, second, there are no specific regulations governing legal protection for a notary, only contained in Article 66 UUJN. Keywords: